Study of lung function on construction workers - K.L, Shobha; Venkatachalam, Subbramaniam; Nair, Ashriina; Elangu, Buwanesswaran; Samuganathan,, Periyaiyadever; Subramanian, Barathi; Rao, Amita Shobha; L, Ramachandra (International Journal of Health, 2017)
Lungs are one of the most vital organs which are responsible for gas exchange during respiration .Lung functions can be compromised in working environment especially at building construction work. The aim of the study was to assess the lung functions of the construction workers.Material and Methods: Adult volunteers who had given consent with a field work experience of minimum 2 years were involved in the study. Validated questionnaire was given to them and the responses were collected .Peak flow meter measurement were also analysed.Results: (65.30%) smokers had a peak flow meter reading of less than 400L and plumbers were the group affected by decreased pulmonary function test followed by mason-helpers.Conclusion: Morbidity among the construction workers varied with type of work at the construction site and comorbid factors such as smoking.